Executive Committee Minutes 2019-03-07 - Academic Senate:::::::::
Agenda – Approved. Minutes of 2/21/19 – Approved. Chair Report. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President for Student Affairs. Associated Students Report. Revision to the Emeritus Policy – referred back to FSAC. From PDS: Resolution for the Creation of an Ombuds Office at Sonoma State University – approved for Senate agenda. From EPC: Revision to Art Studio curriculum – approved for Senate consent calendar. From EPC: Music BM Performance concentration revision – approved for Senate consent calendar. APARC Report. EPC Report. FSAC Report. SAC Report. Rep to SEC Ex Com Report. Senate agenda approved.